Changes in SNI-1726 and SNI-2847’S Effects on Low-Rise Reinforced Concrete Buildings’s Reinforcing Steel Weight - Sutjipto, Suradjin; Sumeru, Indrawati; Sucipto, Shericca Augustin (International Journal Labs, 2023)
The updates of the Indonesian seismic design code (SNI 1726) and the reinforced concrete design code (SNI 2847) have been applied in practice simultaneously. Based on these new codes, seismic loads generally increase, especially for low-rise buildings, and the reinforcement design requirements become much more stringent. Therefore, the construction industry predicts that there will be a significant increase in the need for reinforcing steel. This paper would like to describe the comparison of the design reinforcing steel weight in a 4-story reinforced concrete case study building with a special moment resisting frame system, which is designed using a combination of SNI 1726:2012 and SNI 2847:2013, and which is designed using a combination of SNI 1726:2019 and SNI 2847:2019. This study was found that the increase in reinforcing steel is not proportional to the increase in seismic load and much smaller. This result can then be an illustration of how much increase in design reinforcing steel when using the new codes.